Gender mainstreaming in Zimbabwean state universities: turning dreams into reality? - Chauraya, Efiritha (Unisa Publications, 2016)
This article is part of a larger study carried out by this researcher on gender mainstreaming in Zimbabwean state universities. Although the larger study utilized both qualitative and quantitative analysis, this study is qualitative main, as it sets out to determine the paradigm(s) through which the institutions mainstreamed gender. The qualitative examination revealed that the gender mainstreaming paradigm utilized by Zimbabwean state universities was the Integrationist Women in Development (WID) approach. The paradigm’s transformative potential had driven the institutions to a point of no proficiency in terms of the envisaged gender evolution. The study recommends a paradigm shift in gender mainstreaming in Zimbabwean state universities so that the hopes and dreams for institutional gender equality are turned into reality.